The Influence of Macroeconomic Factors on Market Performance with Return on Assets as Moderation of Conventional Banks at IDX 2020-2023 - Suryawijaya, Hartati; Masman, Ronnie Resdianto (REVITALISASI : Jurnal Ilmu Manajemen, 2025)
This study aims to analyze the effects of credit interest rates, inflation, and bank size on market performance, with Return on Assets (ROA) as a moderating variable. The study uses a sample of 93 conventional banks listed on the Indonesia Stock Exchange (IDX) from 2020 to 2023. Data were analyzed using multiple regression methods with a quantitative approach. The results indicate that credit interest rates and inflation have a negative and significant effect on market performance, while bank size has a positive and significant effect. ROA moderates the relationship between bank size and market performance but does not significantly moderate the effects of credit interest rates and inflation on market performance. This study provides insights for stakeholders in understanding macroeconomic factors that influence banking stability in Indonesia.